On some formation features of the historical memory of the new generations - Myslivets, Nikolay L. (Journal of the Belarusian State University. Sociology, 2020)
The article considers the issues relating to the formation and preservation of the memory of the Great Patriotic War in the minds of younger generations. The results of two studies conducted in 2010 and 2018 were used as the empirical basis. The trends in the historical memory of the war are described, the sources of information, the role of social institutions that have a decisive influence on its formation and functioning are analyzed.